Surgical aortic valve replacement with a stented pericardial bioprosthesis: 5-year outcomes. (5th July 2022) - Klautz, Robert J M; Dagenais, François; Reardon, Michael J; Lange, Rüdiger; Moront, Michael G; Labrousse, Louis; Weissman, Neil J; Rao, Vivek; Patel, Himanshu J; Liu, Fang; Sabik, Joseph F
Abstract: OBJECTIVES: This analysis evaluated the safety, durability and haemodynamic performance of a stented bovine pericardial valve through 5 years of follow-up in patients with an indication for surgical aortic valve replacement. METHODS: Kaplan–Meier analysis was used to estimate the incidence of survival and valve-related thromboembolism, major paravalvular leak, endocarditis, structural valve deterioration (SVD) and reintervention. The mean aortic gradient and New York Heart Association (NYHA) functional class were also evaluated. RESULTS: A total of 1118 patients have received the Avalus valve; 564 have completed the 5-year follow-up. The median follow-up was 4.85 years (4810 patient-years total follow-up). At baseline, the mean age was 70.2 ± 9.0 years; 75.1% of patients were male. The Society of Thoracic Surgeons predicted risk of mortality was 2.0 ± 1.4%. Most patients were in NYHA functional class II (46.8%) or III (40.3%). At the 5-year follow-up, the overall Kaplan–Meier survival rate was 88.1% (85.9–90.0%). The Kaplan–Meier event rates were 5.6% (4.3–7.2%) for thromboembolism, 4.4% (3.2–6.0%) for endocarditis, 0.2% (0.0–0.7%) for a major paravalvular leak and 3.2% (2.3–4.6%) for reintervention. There were no cases of SVD. The mean gradient decreased from 42.1 ± 17.1 mmHg at baseline, to 13.1 ± 4.7 mmHg at discharge and remained stable at 12.5 ± 4.6 mmHg at 5 years. More than 95% of patients were in NYHA functional class I/II 5 years after surgery. CONCLUSIONS: The findings of a high survival rate, excellent safety, no SVD and stable haemodynamic performance and functional status through 5 years of follow-up are encouraging. Additional follow-up is needed to assess the long-term durability of this contemporary surgical bioprosthesis. Abstract : Surgical aortic valve replacement (SAVR) is one of the most frequently performed cardiac operations.